220k views
5 votes
Helppppppp pleaseeeeee

Helppppppp pleaseeeeee-example-1
User Tyreek
by
5.2k points

2 Answers

4 votes
You sub in the numbers on the left column into the equation for x for example the first one is y=9-3(0) and solve for y by multiplying 3 times 0 which is 0 so y=9
User MaxRecursion
by
5.6k points
4 votes

All you have to do is plug in the number for x, and find y. I will write this out as if in that chart you have shown.

x y = 9 - 3x y

_______________________________________

0 y = 9 - 3(0) 9

1 y = 9 - 3(1) 6

2 y = 9 - 3(2) 3

3 y = 9 - 3(3) 0


Hope that helps!!


User Adiboy
by
5.9k points